Insights on Human Small Heat Shock Proteins and Their Alterations in Diseases - Tedesco, B.; Cristofani, R.; Ferrari, V.; Cozzi, M.; Rusmini, P.; Casarotto, E.; Chierichetti, M.; Mina, F.; Galbiati, M.; Piccolella, M.; Crippa, V.; Poletti, A. (Frontiers in Molecular Biosciences, 2022)
The family of the human small Heat Shock Proteins (HSPBs) consists of ten members of chaperones (HSPB1-HSPB10), characterized by a low molecular weight and capable of dimerization and oligomerization forming large homo- or hetero-complexes. All HSPBs possess a highly conserved centrally located alpha-crystallin domain and poorly conserved N- and C-terminal domains. The main feature of HSPBs is to exert cytoprotective functions by preserving proteostasis, assuring the structural maintenance of the cytoskeleton and acting in response to cellular stresses and apoptosis. HSPBs take part in cell homeostasis by acting as holdases, which is the ability to interact with a substrate preventing its aggregation. In addition, HSPBs cooperate in substrates refolding driven by other chaperones or, alternatively, promote substrate routing to degradation. Notably, while some HSPBs are ubiquitously expressed, others show peculiar tissue-specific expression. Cardiac muscle, skeletal muscle and neurons show high expression levels for a wide variety of HSPBs. Indeed, most of the mutations identified in HSPBs are associated to cardiomyopathies, myopathies, motor neuropathies. Instead, mutations in HSPB4 and HSPB5, which are also expressed in lens, have been associated with cataract. Mutations of HSPB family members encompass base substitutions, insertions, and deletions, resulting in single amino acid substitutions or in the generation of truncated or elongated proteins. This review will provide an updated overview of disease-related mutations in HSPBs, focusing on the structural and biochemical effects of mutations and their functional consequences.